Effects of short‐term endurance exercise on gut microbiota in elderly men - Taniguchi, Hirokazu (Physiol Rep, 2018)
Regular exercise reduces the risks for cardiovascular diseases. Although the gut microbiota has been associated with fitness level and cardiometabolic risk factors, the effects of exercise‐induced gut microbiota changes in elderly individuals are unclear. This study evaluated whether endurance exercise modulates the gut microbiota in elderly subjects, and whether these changes are associated with host cardiometabolic phenotypes. In a randomized crossover trial, 33 elderly Japanese men participated in a 5‐week endurance exercise program. 16S rRNA gene‐based metagenomic analyses revealed that the effect of endurance exercise on gut microbiota diversity was not greater than interindividual differences, whereas changes in α‐diversity indices during intervention were negatively correlated with changes in systolic and diastolic blood pressure, especially during exercise. Microbial composition analyses showed that the relative abundance of Clostridium difficile significantly decreased, whereas that of Oscillospira significantly increased during exercise as compared to the control period. The changes in these taxa were correlated with the changes in several cardiometabolic risk factors. The findings indicate that short‐term endurance exercise has little effect on gut microbiota in elderly individuals, and that the changes in gut microbiota were associated with cardiometabolic risk factors, such as systolic and diastolic blood pressure, providing preliminary insight into the associations between the gut microbiota and cardiometabolic phenotypes.